Identifying the similarities and differences between single nucleotide polymorphism array (SNPa) analysis and karyotyping in acute myeloid leukemia and myelodysplastic syndromes - Noronha,Thiago Rodrigo de (2015)
Objective: To standardize the single nucleotide polymorphism array (SNPa) method in acute myeloid leukemia/myelodysplastic syndromes, and to identify the similarities and differ- ences between the results of this method and karyotyping. Methods: Twenty-two patients diagnosed with acute myeloid leukemia and three with myelodysplastic syndromes were studied. The G-banding karyotyping and single nucleotide polymorphism array analysis (CytoScan(r) HD) were performed using cells from bone marrow, DNA extracted from mononuclear cells from bone marrow and buccal cells (BC). Results: The mean age of the patients studied was 54 years old, and the median age was 55 years (range: 28-93). Twelve (48%) were male and 13 (52%) female. Ten patients showed abnormal karyotypes (40.0%), 11 normal (44.0%) and four had no mitosis (16.0%). Regarding the results of bone marrow single nucleotide polymorphism array analysis: 17 were abnor- mal (68.0%) and eight were normal (32.0%). Comparing the two methods, karyotyping identiﬁed a total of 17 alterations (8 deletions/losses, 7 trissomies/gains, and 2 translocations) and single nucleotide polymorphism array analysis identiﬁed a total of 42 alterations (17 losses, 16 gains and 9 copy-neutral loss of heterozygosity). Conclusion: It is possible to standardize single nucleotide polymorphism array analysis in acute myeloid leukemia/myelodysplastic syndromes and compare the results with the abnormalities detected by karyotyping. Single nucleotide polymorphism array analysis increased the detection rate of abnormalities compared to karyotyping and also identiﬁed a new set of abnormalities that deserve further investigation in future studies.